HUBUNGAN PENGETAHUAN REMAJA TENTANG KESEHATAN REPRODUKSI DENGAN SIKAP TERHADAP PERNIKAHAN USIA DINI DI WILAYAH KERJA PUSKESMAS SAMBAU KOTA BATAM - Sari, Juwita; Mona, Silvia; Hafid, Rachmawati Abdul (Universitas Batam, 2021)
Early marriage is still a problem in Indonesia. Marriages carried out at the age of less than 18 years pose health, social and psychological risks. This age should still be in the stage of physical, emotional and social development. Due to these adverse effects, the government has made various efforts, including regulations for limiting the age of marriage and 12 years of compulsory education. The PKPR program was created to appreciate and meet the needs of youth, to achieve optimal growth and development. The purpose of the study was to determine the relationship between adolescent knowledge about reproductive health and adolescent attitudes towards early marriage. This study uses an observational design with a cross sectional approach in the working area of the Sambau Health Center on December 12, 2020-1 January 2021. The population is 1,813 adolescents aged 10-18 years with 100 adolescents as samples taken with the Slovin formula 10-20% of the population. The results of the study of 100 teenagers that 67% of teenagers have good knowledge and have a positive attitude towards early marriage, which means they do not agree with early marriage. There are 16% of adolescents who have low knowledge and agree with early marriage. The conclusion is that there is a relationship between adolescent knowledge about reproductive health and their attitude towards early marriage with the Chi Square test results around p-value 0.000 <0.05. This suggestion, hopefully all levels of society, especially parents can provide knowledge about reproductive health to children from an early age.